The construction and evaluation of a novel tubular photobioreactor at a small pilot plant scale - Kutama, Makonde (Vaal University of Technology, 2012)
The mass production of algae for commercial purposes has predominately been carried out in open ponds systems. However, open ponds systems have a number of disadvantages such as poor light utilization, requirement for large areas of land and high risks of contamination. On the other hand, photobioreactors have attracted much interest because they allow a better control of the cultivation conditions than open systems. With photobioreactors, higher biomass productivities are obtained and contamination can be easily prevented. Photobioreactors can also be engineered to manipulate the light and dark photosynthetic reactions thus enhancing biomass productivity. The main objective of this study was to construct a novel tubular photobioreactor which had the ability to expose the cultured alga to light and dark phases with the aim of optimizing the algal biomass production. A novel tubular photobioreactor with the ability to manipulate the cultured alga’s light and dark photosynthetic reactions was constructed in this study. The alga Spirulina platensis was chosen as the test organism in this novel tubular photobioreactor due to a number of reasons such as its globally socioeconomic importance, its tolerance of higher pH and temperature values which makes it almost impossible to contaminate. The cultivation process of Spirulina in the photobioreactor was investigated through alternating light and dark cycles in an attempt to increase the photosynthetic efficiency of the culture. The effect of different light intensities on the growth of Spirulina in the novel tubular photobioreactor was investigated and it was found that the best light condition that favored higher biomass formation was at 600 μ mol m-2 s-1. Five different light/ dark ratios were evaluated at a light intensity of 600 μ mol m-2 s-1 during a batch mode of operation of the novel tubular photobioreactor. The light/ dark ratio of 1:0.25 was found to be the best ratio because it gave the highest biomass in the shortest period of time when compared to the other ratios used. These results seem to suggest that longer light cycle relative to dark cycle results in higher biomass production. The ratio of 1:0.25 was then used to operate the novel tubular photobioreactor in a continuous mode. A maximum biomass productivity of 25 g/m2/day was achieved which corresponded to a net photosynthetic efficiency of 5.7 %. This result was found to be higher than what most photobioreactors could achieve but it was 2.8 g/m2/day lower than the highest ever reported productivity in a photobioreactor when Spirulina is cultivated. The 2.8 g/m2/day lower was attributed to the different materials used in the construction of these two photobioreactors. The photobioreactor which achieved 27.8 g/m2/day was made up of a clear glass whereas the novel tubular photobioreactor was made up of a PVC tubing. PVC tubes tend to change from clear to a milky colour after a certain period when it is used at higher temperature and pH values hence blocks a certain amount of light. Therefore the main recommendation in this study is to use a PVC tubing with a longer life span when used at a higher temperature and pH values.
M. Tech. (Biotechnology in the Department of Biosciences, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Algae production; Open pond systems; Photobioreactors; Algae cultivation; Spirulina; Biomass productivity; 579.8; Algae -- Biotechnology.; Dissertations, Academic -- South Africa.